Practical and Ethical Concerns in Implementing Enhanced Surveillance Methods to Improve Continuity of HIV Care: Qualitative Expert Stakeholder Study - Buchbinder, Mara; Blue, Colleen; Rennie, Stuart; Juengst, Eric; Brinkley-Rubinstein, Lauren; Rosen, David L (JMIR Publications, 2020)
BackgroundRetention in HIV care is critical to maintaining viral suppression and preventing further transmission, yet less than 50% of people living with HIV in the United States are engaged in care. All US states have a funding mandate to implement Data-to-Care (D2C) programs, which use surveillance data (eg, laboratory, Medicaid billing) to identify out-of-care HIV-positive persons and relink them to treatment. ObjectiveThe purpose of this qualitative study was to identify and describe practical and ethical considerations that arise in planning for and implementing D2C. MethodsVia purposive sampling, we recruited 43 expert stakeholders-including ethicists, privacy experts, researchers, public health personnel, HIV medical providers, legal experts, and community advocates-to participate in audio-recorded semistructured interviews to share their perspectives on D2C. Interview transcripts were analyzed across a priori and inductively derived thematic categories. ResultsStakeholders reported practical and ethical concerns in seven key domains: permission and consent, government assistance versus overreach, privacy and confidentiality, stigma, HIV exceptionalism, criminalization, and data integrity and sharing. ConclusionsParticipants expressed a great deal of support for D2C, yet also stressed the role of public trust and transparency in addressing the practical and ethical concerns they identified.